Metacognition of Working Memory Performance: Trial-by-Trial Subjective Effects from a New Paradigm - Garcia, Andrew C.; Bhangal, Sabrina; Velasquez, Anthony G.; Geisler, Mark W.; Morsella, Ezequiel (Frontiers in Psychology, 2016)
Investigators have begun to examine the fleeting urges and inclinations that subjects experience when performing tasks involving response interference and working memory. Building on this research, we developed a paradigm in which subjects, after learning to press certain buttons when presented with certain letters, are presented with two action-related letters (the memoranda) but must withhold responding (4 s) until cued to emit the response associated with only one of the two letters. In the Congruent condition, the action corresponds to the cue (e.g., memoranda = AB, cue = B, response = B); in the Incongruent condition, the action corresponds to the other item of the memoranda (e.g., memoranda = AB, cue = B, response = A). After each trial, subjects inputted a rating regarding their subjectively experienced “urge to err” on that trial. These introspection-based data revealed that, as found in previous research, urges to err were strongest for incongruent trials. Our findings reveal, first, that subjects can successfully perform this new task, even though it is more complex than that of previous studies, and second, that, in this new paradigm, reliable subjective, metacognitive data can be obtained on a trial-by-trial basis. We hope that our novel paradigm will serve as a foundation for future experimental projects on the relationship between working memory performance and consciousness—an under-explored nexus whose investigation is likely to reveal insights about working memory, cognitive control, and metacognition.